Healthcare service configuration based on project scheduling. (January 2020) - Zhang, Xiaojin; Ma, Shuang; Chen, Songlin
Abstract: Configuration has been recognized as an effective methodology to provide high product variety that caters to individual customer's needs in the manufacturing industry. For healthcare service configuration, this decision-making process can be taken as service package creation and treated analogously as a project, which is defined as a collection of tasks. This research develops a decision support model to integrate individual patients into the healthcare service configuration process. The healthcare service configuration is formulated as a Resource Constrained Project Scheduling Problem (RCPSP), and a bi-level optimization algorithm based on Genetic Algorithm (GA) is developed for problem solving. The methodology and algorithm are implemented with a case study based on the data obtained from a general hospital in Singapore, which has demonstrated the applicability of healthcare service configuration.